Celebrities and Music and Brand Recall Cues - An Experimental Study of TV Commercials - Müllern, Tomas; Irinca, Andreea; Morawietz, Anne; Pajarskaite, Milda (Advances in Social Sciences Research Journal, 2015)
This article reports on an aided brand recall experiment testing the effect of celebrities compared to popular music in TV advertisements. The effect of three cues, celebrity, music, and celebrity + music, was analysed and crosschecked with the moderating effect of familiarity with the cues. The results show a stronger effect of the celebrity cue compared to music. Familiarity with the celebrity leads to higher recall than non-familiarity, whereas the results for familiarity with the music are inconsistent with stronger recall for non-familiar music for some of the cues. The results enrichen the understanding of how celebrities and music can be used as advertising cues.